Diode Laser Clinical Efficacy and Mini-Invasivity in Surgical Exposure of Impacted Teeth. Issue 8 (November 2016) - Migliario, Mario; Rizzi, Manuela; Lucchina, Alberta Greco; Renò, Filippo
Abstract : Abstract: The gold standard to arrange impacted teeth in the dental arch is represented by a surgical approach followed by orthodontic traction force application. In the literature, many surgical approaches are proposed to reach such a scope. The aim of the present study is to demonstrate how laser technique could positively assist surgical approaches. Study population was composed by 16 patients undergoing orthodontic treatment of 20 impacted teeth. In 10 patients (population A) surgical exposure of the impacted teeth was performed using a 980 nm diode laser, while in the other 10 patients (population B), surgical incision was performed using a traditional lancet. Only 3 patients of the population A needed local anesthesia for surgical procedure while the remaining 7 patients reported only faint pain during surgery. Two patients referred postsurgical pain (numerical rating scale average value = 2) and needed to take analgesics. None of the patients showed other postsurgical side effects (bleeding, edema). All population B patients needed infiltrative anesthesia and referred postsurgical pain (numerical rating scale average value >4) treated with analgesics. Moreover, in such population, 4 patients referred lips edema while 4 showed bleeding and 6 needed surgical sutures of soft tissues. The lack of side effects of laser surgical approach to expose impacted teeth must persuade dental practitioners to choose such a clinical approach to closed surgical approach every time it is possible.